Synchronous Learning Model: Innovative Learning Using Saudi Electronic University-Based Learning Management System - Muhammad Sobri; Firman Afrian Pratama; Rofiazka Fahmi Huda; Agung Yusup; Huda Salah Rashid (LISANIA: Journal of Arabic Education and Literature, 2024)
This research aims to explore the implementation of the Synchronous Learning Model (SLM) using a Saudi Electronic University (SEU)-based Learning Management System (LMS), the users’ perceptions, as well as its advantages and disadvantages. A mixed method with a Convergent Parallel model was chosen as the research method, using observation, interviews, and questionnaires distributed to 36 students. Afterward, through the interactive analysis of Miles and Huberman's triangulation, it was discovered that the implementation of SLM with SEU-based LMS in Jambi University was successful, though some challenges, including system weaknesses during evaluation and constraints on internet connectivity, were identified. Therefore, it is recommended that SEU provides improvements to the LMS and the internet access could be improved throughout all regions in Indonesia to facilitate effective and efficient technology utilization in the learning process.